Simulation study on terminal layout in automated container terminals from efficiency, economic and environment perspectives. (1st November 2021) - Li, Xiangda; Peng, Yun; Huang, Jun; Wang, Wenyuan; Song, Xiangqun
Abstract: Terminal layout design is an important strategic decision to obtain efficient automated container terminals. Recently, several types of layout design are being implemented to realize side-loading operations, such as U-type and parallel layout design for bilateral-cantilever automated rail-mounted gantry cranes. However, it is lack of a comprehensive comparation with perpendicular layout design for non-cantilever gantry cranes, which allows end-loading operations. Besides, the impact of layout design on terminal performance, such as annual throughput, ship waiting time and operation efficiency of quay cranes, is still not well understood and needs to be estimated in the planning phases of automated terminals. Thus, this study conducts a detailed simulation research on different types of layout design to compare their terminal performance. Novel agent-based simulation models are developed, which incorporate side-loading and end-loading operations under different types of layout design. And simulation-based energy consumption and cost models are developed to evaluate their energy consumption and total cost. Results indicate that U-type automated terminals gain the lowest energy consumption and operation cost, and outperform those with perpendicular layout in terms of operation efficiency and waiting time in most cases. The valuable reference regarding layout design is identified for terminal operators to make strategic decisions. Highlights: Novel simulation models are developed to comprehensively evaluate layout design in automated terminals. Models consider special operation characteristics, cycle operation processes and many practical settings. Influence factors are identified to improve operation efficiency and reduce waiting time. U-type automated terminals gain the lowest energy consumption and operation cost.